Evaluation of pharmacognostic, phytochemical, antioxidant and anticancer properties of leaves of Cassia tora and Mimusops elengi (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The objective of the present research work was to study the selected medicinal plants regarding their botanical, phytomoieties present, free radical scavenging, and antineoplastic properties of the alcoholic extract of leaves from Mimusops elengi (MEAE) and Cassia tora (CTAE). An attempt was also made to compare the results obtained with proven anticancer marker compounds like Curcumin, Quercetin, Gallic acid, and Ursolic acid. Pharmacognostic studies were conducted using standard methods and protocols. Phytochemical analysis was performed using HPTLC studies. The antioxidant potential of selected plant extracts has been evaluated using a DPPH assay. The selected activity was evaluated using a sensitive and reliable MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay towards MCF-7 (breast), HeLa (Cervical), and HepG2 (liver) cells. Self-programmed Cell death or Apoptosis assay was carried out on MCF-7 cancer cells to explore the possible mechanism of the anticancer effect of these plant extracts. Pharmacognostic evaluations confirmed the identity, quality, and safety of the botanical specimens used. HPTLC analysis revealed distinct phytochemical profiles rich in Gallic acid, Quercetin, Ursolic acid, and similar compounds in both extracts. The study demonstrated concentration-dependent antioxidant activity with MEAE exhibiting stronger activity than CTAE. The results thus obtained in the MTT assay exhibited that cancer cell multiplication of MCF-7, HeLa, and HepG2 cancer cells was prevented by the selected extracts of MEAE and CTAE in a reproducible dose-dependent manner over time. Results of the Apoptosis assay gave the authors a probable thought and direction, that the anticancer activity of CTAE and MEAE towards MCF-7 breast cancer cells may be due to induction of apoptosis.